Automatic Content Marketing With AI for business - fatkhurrahman (Journal of Artificial Intelligence and Development, 2023)
In the realm of content marketing, leveraging the power of artificial intelligence (AI) has become a transformative strategy for generating revenue. By harnessing AI technologies, businesses can enhance their content creation, distribution, and engagement processes, ultimately driving more effective and targeted campaigns. This fusion of marketing and AI opens up new possibilities for personalized content delivery, data-driven insights, and improved customer experiences. As organizations navigate the evolving landscape of digital marketing, integrating AI into content strategies emerges as a pivotal approach to not only stay competitive but also to capitalize on the lucrative potential of content-driven monetization.